The relationship of physique and body composition to strength in a group of physical education students. Issue 4 (December 1980) - Bale, P.
Abstract : Fifty-three specialist women physical education students were measured anthropometrically and from these measurements somatotype and body composition were estimated. Leg, back and grip strength dynamometers were used to measure strength indices. Arm strength was calculated from each subject's pull-ups and push-ups and lung capacity was measured using a spirometer. The somatotype ratings and percent fat measurements indicate that the P.E. students are generally more muscular and less fat for their age than non-P.E. students. There was a strong relationship between percent fat and the endomorphy rating and a moderate relationship between lean body weight and mesomorphy. The moderate relationship of the strength variables with the muscular rating, whether expressed as mesomorphy or lean body weight, suggests that the higher a subject's muscular component the greater their dynamic strength.